Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

An old problem from Whittaker and Watson I'm having issues with. Any guidance would be appreciated.

Show that the function $$ f(x)=\int_0^\infty \left\{ \log u +\log\left(\frac{1}{1-e^{-u}} \right) \right\}\frac{du}{u}e^{-xu} $$ has the asymptotic expansion $$ f(x)=\frac{1}{2x}-\frac{B_1}{2^2x^2}+\frac{B_3}{4^2x^4}-\frac{B_5}{6^2x^6}+\;... \;, $$ where $$B_1, B_3, ...$$ are Bernoulli's numbers.

Show also that f(x) can be developed as an absolutely convergent series of the form $$ f(x)=\sum_{k=1}^\infty\frac{c_k}{(x+1)(x+2)...(x+k)} $$

share|cite|improve this question

Note that: $$\frac{d}{du} \left\{ \ln u + \ln \left( \frac{1}{1- e^{-u}}\right) \right\} = \frac{1}{u} - \frac{1}{e^u - 1} = -\sum_{n = 1}^{+\infty} \frac{B_n u^{n-1}}{n!}$$ then: $$\ln u + \ln \left( \frac{1}{1- e^{-u}}\right) = -\sum_{n=1}^{+\infty} \frac{B_n}{n! \cdot n} u^n $$

so we can rewrite the integral as: $$-\int_0^{+\infty} \sum_{n=1}^{+\infty} \frac{B_n}{n! \cdot n} u^n \cdot \frac{e^{-xu}}{u} \, du = - \sum_{n=1}^{+\infty} \frac{B_n}{n! \cdot n} \cdot \frac{(n-1)!}{x^n} = - \sum_{n=1}^{+\infty} \frac{B_n}{n^2 x^n}$$ In other words it's equal to: $$f(x) = \frac{1}{2x} - \frac{B_2}{2^2 \cdot x^2} + \frac{B_4}{4^2 \cdot x^4} - \ldots$$

I've used the same notation for Bernoulli numbers as it is at MathWorld.

share|cite|improve this answer
Much appreciated. If you have any ideas on the second part of the problem I'd be grateful as well. – John Doe Jun 25 '12 at 4:27

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.